Friends like these ebook A novel. - McCreight, Kimberly (2021)
A GMA Buzz Pick "Kim McCreight's thrillers are smart, propulsive and impossible to put down." —Laura Dave, author of The Last Thing He Told Me In this relentlessly twisty literary thriller from New York Times bestselling author Kimberly McCreight, a desperate intervention brings together a group of college friends 10 years after graduation—a reunion marked by lies, betrayal, and murder. Coming Soon from Amblin Television Six college friends have reunited for a glamorous weekend in the Catskills, a decade after a fatal accident that nearly destroyed them. Keith, once the ringleader of the group, was a handsome charmer on the fast track to success. Now he's spiraling into addiction and stands at the edge of losing it all. This weekend is the last chance to save him. But Keith, it turns out, is not the only one who needs saving. By dawn on Sunday morning, a car has been found deep in the woods—one of the friends is dead, another is missing. When a local detective turns up to investigate, it's clear the group is hiding something ominous. Haunted by her sister's murder years ago, Detective Julia Scutt has her own share of problems. But she's a skilled detective, and knows a rehearsed story when she hears one. It is up to Julia to untangle a decade-long web of friendship, lies and betrayals to discover the truth. But first she needs to face her own past—including the secrets that could, in the end, offer the key to everything. A story of unconditional love, obsession, and the sometimes-impossible choices we have to make in the name of loyalty, Friends Like These is a relentlessly twisty, roller-coaster of a novel.